Optimasi Kualitas Hasil Pengelasan Gas Metal Arc Welding (GMAW) Baja ASTM 283 Grade A dengan RSM (Response Sufrace Methodology) - Gapsari, Femiana; Sulistyorini, Dwi Hadi (Jurnal Rekayasa Mesin, 2011)
This research aimed at the investigation of the effect of welding current, welding voltage, and welding speed on the hardness of weldment. The material used in this research is steel ASTM 283 grade A. An optimization approach is performed in order to determine the variables combination of the welding current, voltage, welding and welding speed to maintain the weldment to be below hardness and was closer with parent metal hardness. With application Response Surface Methodology(RSM) mathematical relationship between the welding process input parameters and output variable like hardness of welded joint in order to determine the welding input parameters that lead to desired weld hardness. RSM design of experiment techniques can be very efficiently used in the optimization of welding parameters in GMAW process. Formulation of equation is done with the help of which hardness can be predicted as Y = 218.624 +10.31 I+1.614V-4.017s-1.723 I2+0.929 s2.Keywords : Optimization, Response Surface Methodology (RSM), Hardnes, GMAW.